Imaging of Orthopedic Sports Injuries - Vanhoenacker, Filip M.; Maas, Mario; Gielen, Jan L.M.A (Diagnostic Imaging, 2007)
This volume provides an updated review of imaging abnormalities in orthopedic sports injuries. The first part of the book contains background information on relevant basic science and general imaging principles in sports traumatology. The second part comprises a topographic discussion of sports injuries. Each chapter highlights the merit of different imaging techniques, focused on a specific clinical problem. In the third part, natural history, monitoring and follow-up by imaging are discussed. This well-illustrated book will be of value for musculoskeletal radiologists, orthopedic surgeons, sports physicians and everyone else involved in sports medicine.